2010
DOI: 10.1016/j.joep.2009.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Does competition enhance performance or cheating? A laboratory experiment

Abstract: Does Competition Enhance Performance or Cheating?A Laboratory Experiment *In this paper we experimentally test whether competing for a desired reward does not only affect individuals' performance, but also their tendency to cheat. Recent doping scandals in sports as well as forgery and plagiarism scandals in academia have been partially explained by "competitive pressures", which suggests a link between competition and cheating. In our experiment subjects conduct a task where they have the possibility to make … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
107
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(120 citation statements)
references
References 28 publications
8
107
3
Order By: Relevance
“…Thus, the greater avoidance of regulation and misreporting by women appears to be context-specific and limited to environments in which women are competitively disadvantaged. In this vein, our results share features with recent findings by Schwieren and Weichselbaumer (2010), who found that women engaged in cheating behavior more often than men, but that this was less related to a gender difference than to differences in ability.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the greater avoidance of regulation and misreporting by women appears to be context-specific and limited to environments in which women are competitively disadvantaged. In this vein, our results share features with recent findings by Schwieren and Weichselbaumer (2010), who found that women engaged in cheating behavior more often than men, but that this was less related to a gender difference than to differences in ability.…”
Section: Discussionsupporting
confidence: 91%
“…It may be argued that the competitive reward structure of our experiment is to blame for driving a large number of subjects to overcome their moral feelings and cheat maximally. However, Schwieren and Weichselbaumer (2010), who used a web maze game to test the hypothesis that competition enhances cheating, did not find a significant difference between the number of mazes falsely reported to have been solved by the competitive and non-competitive treatment. Still, in the computerized maze game subjects could not tell whether or not their competitors were cheating, whereas in our experiment cheaters could easily be seen using their smartphones.…”
Section: Discussionmentioning
confidence: 95%
“…Subjects' self-grading was then compared with their actual scores to reveal cheating. Schwieren and Weichselbaumer (2010) asked 65 students to solve, under competitive and non-competitive settings, as many mazes as they could in a maze game offered on Yahoo's website and record their achievements in a table. Subjects' records were then compared with the number of mazes actually solved using a spyware program that secretly monitored subjects' performance.…”
Section: Introductionmentioning
confidence: 99%
“…Even in ancient Greece and Rome, athletes experimented with substances such as mushrooms or bull's blood in order to increase the likelihood to win sport contests (cf. In addition to theoretical explanations for why athletes cheat, there exists experimental (Schwieren and Weichselbaumer, 2010), qualitative (Smith et al, 2010;Boodworth and McNamee, 2010) as well as non-experimental quantitative (Humphreys and Ruseski, 2011) studies seeking to explain doping prevalence and attitudes. Obviously, athletes view the use of banned performance-enhancing substances as "unnatural" and "cheating," while legal performance-enhancing substances are considered "essential" for success (Smith et al, 2010, p. 181).…”
Section: Performance Enhancing Drugs ("Doping") and Sportsmentioning
confidence: 99%